2016
DOI: 10.1111/bij.12915
|View full text |Cite
|
Sign up to set email alerts
|

One tunic but more than one barcode: evolutionary insights from dynamic mitochondrial DNA inSalpa thompsoni(Tunicata: Salpida)

Abstract: This article has been accepted for publication in the BiologicalFurther investigation revealed that this was due to duplicated and/or minicircular DNAs. These could not simply be explained as artefacts or nuclear copies of mitochondrial DNA, but provided evidence for heteroplasmy arising from a dynamic mitochondrial genome. Genetic variation of this sort may enable S. thompsoni to ecologically benefit from asexually-driven population blooms without incurring the genetic cost of excessive mutational load. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Our results, together with the study presented by Ono & Moteki (2013), has revealed that S. thompsoni appeared across the SB of the ACC, and suggests that presumably it is not a barrier preserving Antarctic waters from S. thompsoni southward migration. A number of genetic studies further proved that salps are highly flexible (Batta-Lona, Maas, O’Neill, Wiebe & Bucklin, 2017; Goodall-Copestake, 2016; Jue et al, 2016), capable of adaptation to the changing environmental conditions within different parts of the Southern Ocean. The comprehensive data about modification of salps/krill population were presented by Ross et al (2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results, together with the study presented by Ono & Moteki (2013), has revealed that S. thompsoni appeared across the SB of the ACC, and suggests that presumably it is not a barrier preserving Antarctic waters from S. thompsoni southward migration. A number of genetic studies further proved that salps are highly flexible (Batta-Lona, Maas, O’Neill, Wiebe & Bucklin, 2017; Goodall-Copestake, 2016; Jue et al, 2016), capable of adaptation to the changing environmental conditions within different parts of the Southern Ocean. The comprehensive data about modification of salps/krill population were presented by Ross et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…The geographical range of crucial Antarctic taxa can move southwards to remain in optimal thermal conditions, squeezing their distribution range closer to the Antarctic continent (Atkinson, Siegel, Pakhomov & Rothery, 2004; Loeb & Santora, 2012; Richardson, 2008; Ross et al, 2014). At the same time, more favorable habitats can be opened for more flexible organisms that are capable of adaptation like gelatinous salps (Goodall-Copestake, 2016; Jue et al, 2016; Mackey et al, 2011; Ross et al, 2014; Steinberg et al, 2015;).…”
Section: Introductionmentioning
confidence: 99%
“…Several genetic studies have revealed that extremely dynamic salp mitochondrial and nuclear DNA result in fast evolutionary rates, which suggests that salps have a high potential for adaptation to various environments (Goodall-Copestake, 2016;Jue et al, 2016). Thus, it is crucial to know how much they can adapt to these harsh environmental conditions, how much their physiological processes and life cycle are inhibited, and whether some degradation of their DNA occurs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the geographic range of E. superba can move southwards to remain in optimal thermal conditions, squeezing their distribution range closer to the Antarctic continent (Atkinson et al, 2004;Richardson, 2008;Loeb & Santora, 2012;Ross et al, 2014). Meanwhile, more favourable habitats can become available for organisms that are capable of adaptation, such as gelatinous salps (Mackey et al, 2011;Ross et al, 2014;Steinberg et al, 2015;Goodall-Copestake, 2016;Jue et al, 2016).…”
mentioning
confidence: 99%
“…Salp genetic studies are in their infancy but it appears that salps possess fast-evolving genes, potentially pointing to a faster turnover rate of the population and an enhanced selection for new life cycle traits (Jue et al, 2016;Batta-Lona et al, 2017;Goodall-Copestake, 2017. It may be hypothesized that salps have a higher capacity to adapt to abrupt shifts in the environment (Bucklin et al, 2018;Bitter et al, 2019).…”
Section: Resiliencementioning
confidence: 99%